Profil Literasi Matematika Siswa SMP Negeri 19 Palu dalam Menyelesaikan Soal Statistika Ditinjau dari Gaya Belajar Visual dan Auditorial - Siti Maysarah; Bakri Mallo; Sutji Rochaminah (Universitas Tadulako, 2022)
This study aims to obtain a description or description of the mathematical literacy of class VIIIA students of SMP Negeri 19 Palu on statistical material. This type of research is descriptive with a qualitative approach. The subjects of this study were students of class VIIIA SMP Negeri 19 Palu who had a visual learning style with the initials ID and auditory with the initials FR. Data was collected through written tests and interviews. The results of this study indicate that the profile of students who have a visual learning style (ID) in solving statistical problems are: (1) ID identifies any information that is known and asked in the question; (2) ID writes down known data using symbols and writes the average in the form of verbal sentences; (3) ID uses the mean or mean formula and substitutes the appropriate data; (4) ID writes the conclusion correctly. Then, the results of this study also show that the profiles of students who have an auditory learning style (FR) in solving statistical problems are: (1) FR identifies any information that is known and asked in the question; (2) FR writes down the known and average data in the form of verbal sentences; (3) FR uses the mean or mean formula and substitutes the appropriate data; (4) FR writes the conclusion correctly.